Anti-radar application of multiwalled carbon nanotubes and zinc oxide synthesized using a hydrothermal method. (16th October 2020) - Subagio, Agus; Kholil, Muhamad Abdul; Ristiawan, Wahyu; Priyono, Priyono
Abstract: Anti-radar technology is essential to reinforce countries defense capacity. Previous studies have shown how the combination of a resistive material with a magnetic one is a good option for the development of radar absorbing materials. Multiwalled carbon nanotube (MWCNT)/ZnO material with MWCNT percentage variations of 1, 3, 5, and 7% has been proposed as a promising material in anti-radar technology. ZnO that is used in the synthesis of MWCNT/ZnO material resulting from a hydrothermal method was prepared using ZnSO4 and Na2 CO3 as precursors. X-ray diffractograms show hexagonal phases for both MWCNT and ZnO, in the latter case hexagonal wurtzite. SEM analysis shows micrometer sheets for ZnO. The VNA test in the X-band frequency range (8 − 12.5 GHz) provides the reflection loss values. Based on the reflection loss value, MWCNT/ZnO material has an optimum absorption value of electromagnetic waves with a percentage of 3% MWCNT at a frequency of 11.2 GHz with an RL value of −31.4535 dB and a percentage of 7% MWCNT at a frequency of 11.2 GHz with an RL value of −25.3897 dB.